Effectiveness of Tamarind Peel (Tamarindus indica L.) Against Staphylococcus aureus Using Different Extraction Methods - Andi Indrawati; Suherman Baharuddin; Nindia Reski Ardila A (International Journal of Scientific Multidisciplinary Research, 2023)
This study aims to determine the effectiveness of tamarind rind against the growth of Staphylococcus aureus using different extraction methods. The research method is a laboratory experimental study to test the effectiveness of Tamarind peel (Tamarindus indica L.) against Staphylococcus aureus using different extraction methods, namely the maceration method and the soxhletation method. The results showed that the extract from the rind of Tamarind (Tamarindus indica L.) was effective in inhibiting the growth of Staphylococcus aureus using either maceration or soxhletation extraction methods. The most effective concentration is at a concentration of 0.8% w/v with a Sig value. 0.000 < 0.05 (Oneway Anova α = 0.05) in the strong category of inhibition (10 – 20 mm)